Financial Integration in Central America : Prospects and Adjustment Needs - Canales Kriljenko, Jorge (IMF Policy Discussion Papers; Policy Discussion Paper ;, 2003)
We assess the current barriers to trade in financial services in the six Central American countries seeking a free trade agreement with the United States (the CAFTA) and examine the relative merits of regional and multilateral liberalization. Even though there are few formal barriers, deficiencies in regulatory and competition standards and in the judicial systems still restrict the participation of foreign institutions in the financial systems in the region. A greater presence of such institutions could support other objectives of trade and investment liberalization, though it would require several adjustments in prudential supervision at national levels and greater cooperation between members of the CAFTA.